Burden of untreated transthyretin amyloid cardiomyopathy on patients and their caregivers by disease severity: results from a multicenter, non-interventional, real-world study - Lucia Ponti; Kristen Hsu; Thibaud Damy; Eduardo Villacorta; Nicolas Verheyen; Denis Keohane; Ronnie Wang; Monica Ines; Nisith Kumar; Carmen Munteanu; Francesco Cappelli (Frontiers in Cardiovascular Medicine, 2023)
BackgroundThe humanistic burden of transthyretin amyloid cardiomyopathy (ATTR-CM) is poorly defined.MethodsAn international study to comprehensively characterize the burden of ATTR-CM on patients naïve to disease-modifying therapy and their unpaid primary caregivers using study-specific and established surveys (patients: Kansas City Cardiomyopathy Questionnaire Overall Summary [KCCQ-OS], 12-Item Short Form Health Survey [SF-12], Hospital Anxiety and Depression Scale [HADS], Patient-Reported Outcomes Measurement Information System [PROMIS] Fatigue and Dyspnea; caregivers: SF-12, HADS, PROMIS Fatigue, Zarit Burden Interview [ZBI]). All data were summarized descriptively.Results208 patient and caregiver pairs were included. 86% of patients were male, median age was 81 years, and 91% (141/155 with genetic testing) had wild-type ATTR-CM. Patient responses characterized the mental and physical burden of ATTR-CM, which was numerically higher among those who were New York Heart Association (NYHA) class III (n = 43) vs. class I/II (n = 156). NYHA class III patients had particularly low KCCQ-OS (36) and SF-12 physical component (27) scores, and 67% had a HADS depression score ≥8. Caregivers (median age 68 years; 85% female; 59% spouse of the patient; median duration of caregiving 1.5 years) reported that NYHA III patients more frequently required help with a range of physical activities than NYHA class I/II patients. 51% of caregivers to NYHA class III patients reported at least a mild-to-moderate burden in the ZBI. A plain language summary of this paper can be found as a supplemental material.ConclusionsUntreated ATTR-CM is a burden to both patients and their caregivers.